Bismuth oxide nanoparticles as agents of radiation dose enhancement in intraoperative radiotherapy. Issue 3 (1st February 2021) - Alyani Nezhad, Zahra; Geraily, Ghazale; Hataminia, Fatemeh; Parwaie, Wrya; Ghanbari, Hossein; Gholami, Somayeh
Abstract : Purpose: Intraoperative radiotherapy (IORT) technique is an advanced radio therapeutic method used for delivery of a single high‐dose radiation during surgery while removing healthy tissues from the radiation field. Nowadays, growing attention is being paid to IORT for its low‐energy (kilovoltage) delivery as it requires less radiation protection, but suffers several disadvantages, including high‐dose delivery and prolonged treatment time. The application of nanoparticles with high atomic number and high attenuation coefficients in kilovoltage energy may help overcome the mentioned shortcomings. This study was designed to investigate and quantify the mean dose enhancement factor (DEF) in the presence of nanoparticles using IORT method. Methods: Bismuth oxide nanoparticles (Bi2 O3 NPs), both in sheet and spherical formats, were synthesized using a novel hydrothermal method and characterized with x‐ray diffraction (XRD), transmission electron microscopy (TEM), and Brunauer–Emmett–Teller (BET) analysis. Genipin‐gelatin gel dosimeter (GENIPIN) was produced in three batches of pure with sheet and with spherical nanoparticles in concentration of 46.596 µg/ml, and irradiated with 50 kV x‐rays. Results: Samples were scanned by a spectrophotometer, which indicated a DEF of 3.28  ±  0.37 and 2.50  ±  0.23 for sheet and spherical NPs, respectively. According to the results of this study, GENIPIN is a suitable dosimeter for the evaluation of three‐dimensional dose distribution in the presence Bi2 O3 NPs. Conclusion: As a result, IORT along with Bi2 O3 NPs has the potential to reduce treatment time and/or normal tissue dose; moreover, it could provide localized dose enhancement.